Denise Austin. Quick burn cardio [videorecording (DVD)] - Austin, Denise; Pozo, Cal (Lions Gate, 2010)
Melt inches faster than ever with two cardio circuit-training workouts that use powerful compound exercises to blast more fat in less time. First, give your burn a boost with Interval Training designed to crush mega calories, then add weights with Cardio Weight Training to sculpt your body slim. Turn up the burn and transform your body today! Segments include: a warm-up, interval training, cardio weight training, and a cool down.